A DFT Study of the Structures and Photoelectric Properties of Benzodithiophene‐Based Molecules by Replacing Sulfur with a Variety of Heteroatoms (O, N, P, Si, Se). Issue 13 (10th May 2017) - Li, Shan; Li, Yuanzuo; Song, Peng; Ma, Fengcai; Yang, Yanhui
Abstract: The sulfur atoms on TIB were replaced by oxygen, nitrogen, phosphorus, silicon and selenium atoms to design a serial of new molecules. The bond lengths, dihedral angles, energy levels and energy gaps, ionization potentials, electron affinities, frontier molecular orbitals, absorption and fluorescence spectrums, reorganization energies and charge transfer rates of all molecules were calculated with density functional theory and the time‐dependent density functional theory methods. The results indicated that the structure and photoelectric properties of TIB have obvious changes after atoms substitution. Both sides of the structures of the designed molecules are distorted obviously. The energy levels, energy gaps, ionization potentials and electron affinities, adsorption and fluorescence spectrums, charge transfer and recombination rates of TIB−P and TIB−Si are better than that of other molecules. It is found that proper atoms substitution can effectively improve the photoelectric properties. Abstract : The oxygen, nitrogen, phosphorus, silicon and selenium atoms were used to replace the four sulfur atoms on both sides of TIB, and simulated their photoelectrical properties. The results indicate that the structures on both sides of the designed molecules are distorted obviously, and the photoelectrical properties of TIB−P and TOB−Si are better than those of other molecules.